Cost profiles of cancer patients at the end of life: Estimates from the EPICOST-study. - Stefano Guzzinati; Alessandra Andreotti; Tania Lopez; Silvia Gori; Alberto Gagliani; Sandra Mallone; Daniela Pierannunzio; Andrea Tavilla; Alessandra Buja; Manuel Zorzi; Silvia Francisci (PLoS ONE)
Objectives The study aims to analyze care and cost patterns in the Veneto region for cancer patients in the final phase of their disease. Methods The study cohort includes adult patients alive on 1.1.2018, which have been diagnosed with cancer at the age 15+ in a 28-years period, spanning from 1990 to 2017, and died within 12 months from prevalence date. The end-of-life (EOL) prevalent cases included in the study cohort are identified by the Veneto Tumor Registry. Primary tumors considered in the analysis are colon, rectum, skin melanoma, female breast, thyroid. Patient monthly average EOL costs, patient annual average EOL costs and total regional costs have been estimated separately for each cancer site/sex/age group/health care service database. Results The estimated EOL total cost, for the five analyzed cancer types in the Veneto Region, is approximately 53 million euros. Costs associated with cancer treatment tend to increase in the final phase of the disease. In general, Hospital Admission is the main driver cost in all types of cancer considered, with the only exception in melanoma, where Hospital Drugs features the highest contribution. Moreover, costs differ significantly depending on the type of cancer, gender, and age, revealing highest average costs associated with younger patients. Conclusions This study provides a comprehensive analysis of healthcare budget distribution in the last year of life, enabling healthcare planners to predict cancer burden in the future. This model can be applied to other Italian regions and countries with different healthcare systems.